Controlling morphological and electro-optical properties via the phase separation in polymer/liquid-crystal composite materials. Issue 2 (26th January 2020) - Li, Ke; Jiang, Haodong; Cheng, Ming; Li, Yifei; Yin, Zhen; Luo, Dan; Sun, Xiao Wei; Liu, Yan Jun
ABSTRACT: The polymer/liquid-crystal composite materials have been extensively studied for their potential applications. Various optical devices based on this composite material have been proposed and realised. The device performance is highly dependent on the phase separation of this composite material. Here, we investigate the photopolymerisation-induced phase separation in this composite material. Depending on the mass ratios between the polymer and the liquid crystal, the phase separation can be well controlled and subsequently affect the morphological and electro-optical properties. At a fixed ratio, we can realise either phase-separated composite films or conventional polymer-dispersed liquid crystal films with completely different optical properties. By carefully controlling the exposure conditions, the morphologies and electro-optical properties have been studied and optimised in details. With in-depth studies and optimisation, the photopolymerisation-induced phase separation technique could be utilised to realise many different optical functions based on the polymer/liquid-crystal composite materials. Graphical Abstract: uf0001 Great morphological changes demonstrated by the NOA65/E7 samples that were fabricated at different temperatures of (a) 30°C, (b) 35°C, (c) 40°C, (d) 45°C, and (e) 50°C with the fixed exposure intensity of 10 mW/cm 2 . (f) Cross-sectional view of the corresponding sample (e).